The Debt-Revenue Nexus: Government Borrowing and the Crowding-Out of Capital Expenditure in Nepal - Aryal, Nikita (Journal of Multidisciplinary Research Advancements, 2026)
This study explores the relationship between government debt and fiscal operations in Nepal. The study employs Ordinary Least Squares (OLS) regression analysis using time-series data from 2005 to 2024. The findings suggest that both domestic and foreign debt have a significant positive effect on tax revenues, particularly excise duties, direct taxes, and total revenue. However, the analysis reveals no statistically significant relationship between government debt (domestic or foreign) and capital expenditure. Contrary to the conventional "crowding-out" hypothesis, this null finding indicates that debt accumulation does not directly reduce public investment, nor does it increase it. The results highlight a disconnect in which borrowed funds and the additional revenues they generate are absorbed by recurrent obligations, particularly debt servicing, rather than being channelled into long-term infrastructure and development projects. This study underscores the importance of strengthening domestic revenue mobilisation and managing debt sustainability while cautioning against overstating the crowding-out effect in the absence of negative empirical coefficients. The findings offer valuable policy insights for Nepal, emphasising the need for diversified revenue sources, efficient debt management, and direct institutional linkages between borrowing and capital budgeting to support sustained economic growth.